(untitled) (Research, Society and Development, 2023)
Tourette Syndrome (TS) is an early childhood disorder, marked by the presence of multiple motor tics and at least one vocal tic, which, sometimes, can be accompanied by psychiatric comorbidities, Attention Deficit Hyperactivity Disorder (ADHD) and Obsessive-Compulsive Disorder (OCD). The objective was to carry out an analysis of studies that refer to the treatments currently available for TS, analyzing the priority of recommendation, its effectiveness, its possible harm and its contribution to improving the quality of life of patients. This is a literature review about the main treatments available for TS. The descriptors “tourette syndrome”, “treatments”, “drug therapy” and “obsessive compulsive disorder” were crossed in the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMed), EbscoHost and Google Scholar. It has been found that initial treatment for Tourette’s Syndrome should be based on Supportive Therapy along with the first line of treatment, with behavioral intervention. If there are no results in reducing tics, the second line of treatment, pharmacological intervention, should be implemented. On the other hand, the third line of treatment, is recommended in about 5% of cases of TS, cases in which previous treatments, like non-drug therapies and drugs, did not have the desired effect. Several lines of treatment act to alleviate the symptoms, thus, the treatment can be characterized as being multifaceted and individualized, as it needs to be developed taking into account the individual’s specifications and the expressions of the disease on him.